Concurso Beleza Negra da Maloca : representações acerca da ideia de África em Aracaju/SE - Menezes, Tacyane Lima de (2013)
This work is part of a larger problem about the questions on ethnicity, whose analytical approach is made from the universe maroon, located in a "space" can be understood as "ethnic" and "urban". The research enters narratives about social practices symbolically experienced from their symbolic modalities of negotiation with reality in a "space" practiced, which is based on invented traditions that reveal strategies to produce ways of life, which distinguish this urban group as a community. In this sense, there is the production of an identity sometimes experienced when defined practices of daily life, where space happens to be experienced by the daily rituals at the same time they are transmitted to the new generations, creating and maintaining a sense of belonging in relation to space, and their collective representations, including that by transiting uses attributed by residents and their other name given to the place.Now thematized, when through the Black Beauty contest CRILIBER, builds a strategy to put a public social situation, which is based from the construction of a sense of belonging to the space where the maroon is concerned, as a way of claiming through building networks of sociability, they carry a double meaning to give greater visibility to the quilombo Longhouse, thus enabling the strengthening among residents' sense of belonging to the place.